EFFECT OF MATERNAL ANAEMIA ON FETAL PARAMETERS - KHAN, MUHAMMAD MUNEEB (Journal of Ayub Medical College Abbottabad, 2001)
Background: A cohort study of anaemic pregnant women was carried out at the Department of Obstetrics and Gynecology, Women and Children Hospital. Abbottabad. from November 30, 1992 to March 30. 1993. to determine the effects of antenatal maternal anaemia on the newborn babies. Methods: 34 pregnant women with anaemia and 39 non-anaemic pregnant women were included in the study. Parameters studied were Hemoglobin levels, RBC morphology. Foetal birth weights. Foetal gestational ages, and Foetal APGAR score (at birth and after 10 months). Results: Out of 34 anaemic women, 6 delivered at 7 or 7+ months, 7 at 8 or 8+ months and 21 at 9 or 9+ months, as compared to 39 non-anaemic, one of whom delivered at 7 or 7 t months, 2 at 8 or 8 + months and 36 at 9 or 9+ months. Fetal mortality rate for anaemic women was 50% at 7 or 7+ months, 28.7% at 8 or 8+ months and 23.80% 9 or +-9 months. For all non-anaemic women, it was 0%. Mean fetal birth weight in anaemic group was 1.4 + 0.66 kg at 7 or 7+ months, 1.93+ 0.53 kg at 8 or 8+ months and 2.61± 0.3 I kg at 9 or 9+ months. Among non-anaemic group, it was 2.8 kg at 7 + months, 3.75± 0.55 kg at 8 or 8+ months and 3.65 ± 0.66 kg at 9 or 9+ months. Conclusions: These findings show that mothers with nutritional or iron deficiency anaemia tend to deliver prematurely with low birth weight babies and a high mortality rate or stillbirths, as compared to non-anaemic mothers.